Integrated adsorption, kinetic–thermodynamic, and computational assessment of cestrum nocturnum as a green corrosion inhibitor for Carbon Steel in 1 M HCl - Silas Oseme Okuma; Martins Obaseki (Chemical Thermodynamics and Thermal Analysis, 2025)
This study investigates Cestrum nocturnum leaf extract (CNLE) as an eco-friendly corrosion inhibitor for carbon steel in 1 M HCl. The extract was characterized using Fourier-transform infrared spectroscopy (FTIR) and thermogravimetric/differential thermal analysis (TGA/DTA). Corrosion inhibition was assessed via gravimetric analysis and atomic absorption spectrometry, while the interaction mechanism was evaluated using quantum chemical (DFT) and molecular dynamics (MD) simulations.FTIR analysis identified O–H/N–H, carbonyl, and aromatic functional groups capable of strong adsorption onto iron surface sites. TGA/DTA confirmed the extract's thermal stability below 100 ◦C, a relevant range for industrial processes like acidizing and flowline operations. Thermometric and gravimetric tests demonstrated clear concentration-dependent inhibition, with efficiencies reaching 94.41 % (thermometric) and 92.44 % (gravimetric) at 0.8 g L⁻¹.Adsorption data were well-described by both Langmuir and Freundlich isotherms (R² up to 0.998). The negative ΔGads values indicated a spontaneous adsorption process, and the magnitudes suggested a mixed physisorption–chemisorption mechanism. Thermo dynamic activation and adsorption parameters further corroborated an endothermic process with combined physical and chemical interactions.DFT and MD simulations of the dominant constituents, oleic acid and piperidine, revealed strong electron-donating character, favorable adsorption geometries, and robust binding on the Fe(110) surface, aligning with the experimental observations.In conclusion, CNLE presents a novel, plant based corrosion inhibitor for carbon steel. It emerges as a promising and sustainable alternative to conventional synthetic inhibitors for mitigating corrosion in acidic environments such as pickling and oil-well acidization.
Keywords: Cestrum nocturnum; Carbon steel corrosion; Green corrosion inhibitor; Chemi-physisorption mechanism; Computation studies